Light and Cognition: Roles for Circadian Rhythms, Sleep, and Arousal - Fisk, Angus S.; Tam, Shu K. E.; Brown, Laurence A.; Vyazovskiy, Vladyslav V.; Bannerman, David M.; Peirson, Stuart N. (Frontiers in Neurology, 2018)
Light exerts a wide range of effects on mammalian physiology and behaviour. As well as synchronising circadian rhythms to the external environment, light has been shown to modulate autonomic and neuroendocrine responses as well as regulating sleep and influencing cognitive processes such as attention, arousal and performance. The last two decades have seen major advances in our understanding of the retinal photoreceptors that mediate these non-image forming responses to light, as well as the neural pathways and molecular mechanisms by which circadian rhythms are generated and entrained to the external light/dark (LD) cycle. By contrast, our understanding of the mechanisms by which lighting influences cognitive processes are more equivocal. The effects of light on different cognitive processes are complex. As well as the direct effects of light, indirect effects may also occur due to disrupted circadian entrainment. Despite the widespread use of disrupted LD cycles to study the role circadian rhythms on cognition, the different experimental protocols used have subtly different effects on circadian function which are not comparable. Moreover, these protocols will also disrupt sleep and alter physiological arousal, both of which are known to modulate cognition. Studies have used different behavioural assays which are dependent upon different cognitive and sensory processes, which may also contribute to their variable findings. Here we propose that studies addressing the effects of different lighting conditions on cognitive processes must also account for their effects on circadian rhythms, sleep and arousal if we are to fully understand the physiological basis of these effects.